Preparation method of waterproof and anti-corrosion fire-retardant module

By preparing modified flame retardants and modified graphite, and blending with modified vermiculite, aluminum chloride and explosion-proof fibers, the existing fire retardant modules have been solved, and the overall performance of the material has been significantly improved.

CN119842124AInactive Publication Date: 2025-04-18LIAONING HENGJIUST FIRE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510340476.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fire retardant modules have insufficient fire retardant performance and acid and alkali resistance in extreme environments, especially the vermiculite and perlite materials used are prone to expand at high temperatures, resulting in structural damage.

Method used

By preparing a modified flame retardant and grafting it onto the modified graphite, flame retardant graphite is obtained and blended with modified vermiculite, aluminum chloride and explosion-proof fibers to form a composite material to enhance the performance of the flame retardant module.

Benefits of technology

It significantly improves the water, acid, alkali and fire resistance of the fire resistance module, enhances the mechanical properties and stability of the material, reduces the thermal expansion coefficient and the polarity of the material surface, and improves the hydrophobicity and fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a preparation method of a waterproof and anti-corrosion fire-retardant module, belongs to the technical field of module preparation, and aims to solve the technical problem that the fire-retardant performance and the acid and alkali resistance of a fire-retardant module in the prior art need to be further improved. The preparation method comprises the following steps: adding modified graphite, a modified flame retardant, aluminum chloride and toluene into a reaction kettle, raising the temperature of the reaction kettle to 40-50 DEG C, carrying out heat preservation reaction for 1-2 hours, and carrying out post-treatment to obtain flame-retardant graphite; the flame-retardant graphite is obtained by preparing the modified flame retardant and grafting the modified flame retardant on the modified graphite, the flame-retardant graphite and siloxane structure can promote the composite performance of the composite vermiculite and the mechanical performance of the explosion-proof fiber, meanwhile, the preparation process of the explosion-proof fiber is promoted, and finally, the explosion-proof fiber is prepared through synergistic cooperation of the materials. And the performance of the fire-retardant module is obviously enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of module preparation, and in particular to a method for preparing a waterproof and anti-corrosion fire-retardant module. Background Art

[0002] Waterproof and anti-corrosion fire-blocking modules have developed from traditional fire-blocking materials and have evolved from a single fire-blocking function to a multifunctional composite material. Early fire-blocking modules were mostly made of inorganic materials, lacking waterproof and anti-corrosion properties and limited in scope of application. With the development and progress of technology, modified polymer materials have been introduced to gradually improve the waterproof and corrosion resistance of the modules. Through composite structure and other technologies, the integration of waterproof and anti-corrosion functions has been achieved, greatly enhancing the stability of the fire-blocking modules in acidic, alkaline and high-humidity environments. At this stage, the introduction of new polymer materials and high-temperature resistant ceramics not only enhances the fire-blocking properties, but also keeps the modules stable under extreme temperatures.

[0003] Prior art CN101798195B discloses a thermosetting resin-based fire-retardant module, which is prepared by uniformly mixing 12-18 parts by weight of a heat-resistant resin, 97-103 parts by weight of an inorganic refractory material, 1.2-1.8 parts by weight of a silicone surfactant and 1.2-1.8 parts by weight of monofluorodichloroethane, adding 12-18 parts by weight of a curing agent, and then curing and pressing to form a thermosetting resin-based fire-retardant module, wherein the heat-resistant resin is one, two or three of a foamable phenolic resin, a foamable melamine formaldehyde resin and a foamable urea-formaldehyde resin, and the inorganic refractory material is a mixture of one of raw vermiculite and perlite and one of cooked vermiculite and expanded perlite, and the weight ratio is 5:95.

[0004] However, the reaction of the above patent content is to mix and cure the heat-resistant resin and inorganic materials to obtain a thermosetting resin-based fire-retardant module. However, the inorganic materials used are vermiculite and perlite, which have poor water resistance and acid and alkali resistance, resulting in the acid and alkali resistance of the module to be further improved. In addition, vermiculite and perlite are very easy to expand at high temperatures, thereby destroying the structure of the module, and ultimately resulting in the fire-retardant performance of the module to be further improved. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a waterproof and anti-corrosion fire-retardant module, which is used to solve the technical problem in the prior art that the fire-retardant performance and acid and alkali resistance of the fire-retardant module need to be further improved.

[0006] The purpose of the present invention can be achieved by the following technical solution: A method for preparing a waterproof and anti-corrosion fire-retardant module, comprising the following steps: S1. Add diallylamine, di(pentafluorophenyl)borane, bis(3,5-xylyl)phosphine, chloroplatinic acid and dimethyl sulfoxide into a reactor, raise the temperature of the reactor to 60-80°C, keep the reaction temperature for 1-2h, and post-treat to obtain a modified flame retardant; The reaction equation for preparing the modified flame retardant is: Where: ; ; “*” indicates the active linking site of organic matter.

[0007] The reaction principle for preparing the modified flame retardant is as follows: by controlling the dosage ratio of the reactants, and under the promotion of chloroplatinic acid and high temperature, the double bond on diallylamine, the boron-hydrogen bond on di(pentafluorophenyl)borane, and the phosphorus-hydrogen bond on bis(3,5-xylyl)phosphine undergo addition, and finally the modified flame retardant is prepared. The mass spectrometry analysis data of the modified flame retardant are: m / z: 685.4 (100.0%), 686.1 (35.9%), 684.3 (22.7%), 686.9 (6.4%).

[0008] S2, adding modified graphite, modified flame retardant, aluminum chloride and toluene into a reactor, raising the temperature of the reactor to 40-50° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain flame retardant graphite; The reaction equation for preparing flame retardant graphite is: In the formula: ” indicates modified graphite.

[0009] The reaction principle for preparing flame-retardant graphite is as follows: under the catalysis of Lewis acid, the secondary amine group of the modified flame retardant undergoes nucleophilic substitution with the ketone group of the modified graphite to generate α-amino alcohol. After that, the nitrogen atom is no longer connected to a hydrogen atom, and the hydroxyl group can only be eliminated with the hydrogen on the α-carbon of the carbonyl group to generate an enamine structure containing a C=C double bond.

[0010] S3, adding modified vermiculite, flame retardant graphite and N, N-dimethylformamide into a reactor, stirring at room temperature for 10-15 minutes, adding vinyl silicone oil, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and azobisisobutyronitrile into the reactor, raising the temperature of the reactor to 60-80°C, keeping warm and stirring for 2-4 hours, and post-treating to obtain composite vermiculite; The reaction equation for preparing composite vermiculite is: In the formula: ” indicates modified vermiculite; ; ; “*” indicates the active linking site of organic matter.

[0011] The reaction principle for preparing composite vermiculite is as follows: under the catalysis of a free radical initiator, double bonds on modified vermiculite, flame retardant graphite, vinyl silicone oil and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione are broken to generate free radicals, and composite vermiculite is obtained through free radical polymerization.

[0012] S4. Add composite vermiculite and flame-retardant graphite into a stirring kettle, gradually add chloroprene latex and explosion-proof fiber into the mixture during stirring, add the mixture into a mold after mixing evenly, and shape it under high temperature and high pressure to obtain a fire-retardant module.

[0013] Further, in step S1, the amount ratio of diallylamine, di(pentafluorophenyl)borane, bis(3,5-xylyl)phosphine, chloroplatinic acid and dimethyl sulfoxide is 1.1g:3.8g:2.4g:0.1-0.3g:21-27mL, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reaction solution is distilled under reduced pressure until no liquid is extracted to obtain a modified flame retardant; Further, in step S2, the amount ratio of modified graphite, modified flame retardant, aluminum chloride and toluene is 5-6g:2-3g:0.3-0.5g:27-33mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed with ethanol and deionized water for 3-5 times, and then the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight to obtain flame retardant graphite; Further, in step S3, the amount ratio of modified vermiculite, flame retardant graphite, N,N-dimethylformamide, vinyl silicone oil, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and azobisisobutyronitrile is 4-5g:2-3g:80-100mL:20-30mL:3-4g:1.6-1.8g, and the post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and after reduced pressure distillation until no liquid is produced, the material is transferred to a mill and ground through a 1000-1200 mesh sieve to obtain composite vermiculite; Furthermore, in step S4, the usage ratio of composite vermiculite, flame retardant graphite, chloroprene latex and explosion-proof fiber is 25-34g:8-15g:45-55g:2-3g.

[0014] Further, the preparation method of modified vermiculite comprises the following steps: A1. After transferring the vermiculite into a crucible, the crucible is placed in a tubular furnace at a temperature of 800-900° C. and a nitrogen atmosphere for 80-90 seconds, and then post-processed to obtain expanded vermiculite; A2. Add expanded vermiculite, vinyl triethoxysilane, anhydrous ethanol and deionized water into a reactor, stir for 5-10 minutes at room temperature, increase the temperature of the reactor to 40-60°C, add sodium hydroxide powder into the reactor to adjust the pH value of the reaction system to 9-10, keep warm and stir for 40-60 minutes, and perform post-treatment to obtain modified vermiculite.

[0015] The reaction principle for preparing modified vermiculite is as follows: after the vermiculite is expanded at high temperature, it is ground to obtain expanded vermiculite, and finally modified by vinyltriethoxysilane to obtain modified vermiculite.

[0016] Further, in step A1, the post-treatment includes: after the standing is completed, the material temperature is transferred to a grinder after it is lowered to room temperature, and ground through a 600-800 mesh sieve to obtain expanded vermiculite; Furthermore, in step A2, the amount ratio of expanded vermiculite, vinyltriethoxysilane, anhydrous ethanol and deionized water is 2-3g:2-3mL:50-60mL:20-30mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3-5 times with ethanol and deionized water, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight to obtain modified vermiculite.

[0017] Further, the preparation method of modified graphite comprises the following steps: B1. Add graphite and 98.0wt% concentrated sulfuric acid into a reactor and stir. Add potassium permanganate powder into the reactor during stirring. Stir for 5-10 min at room temperature. Then, raise the temperature of the reactor to 30-45°C, keep stirring for 2-3 h, and perform post-treatment to obtain graphite oxide. B2. Add graphite oxide, 3-(trimethoxysilyl)propyl 3-oxobutyrate, saturated sodium hydroxide solution, deionized water and anhydrous ethanol into a reactor and stir. Raise the temperature of the reactor to 40-50° C., keep stirring for 30-40 minutes, and perform post-treatment to obtain modified graphite.

[0018] The reaction principle for preparing modified graphite is as follows: under acidic conditions, potassium permanganate introduces a large number of active functional groups such as epoxy, hydroxyl and carboxyl groups on the surface of graphite oxide to obtain graphite oxide, and under alkaline conditions, 3-(trimethoxysilyl)propyl 3-oxobutyrate is used to modify the surface of graphite oxide to finally prepare modified graphite.

[0019] Further, in step B1, the amount ratio of graphite, 98.0wt% concentrated sulfuric acid and potassium permanganate is 1-2g:25-40mL:5-10g, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, 30wt% hydrogen peroxide aqueous solution is added to the reactor until the solution fades from deep purple, and the pH of the reaction solution is adjusted to 7 with a saturated sodium hydroxide solution, the reaction solution is filtered to collect the filter cake, the filter cake is washed 3-5 times with ethanol and deionized water, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight, and then the material is transferred to a mill and ground through a 600-800 mesh sieve to obtain graphite oxide; Furthermore, in step B2, the amount ratio of graphite oxide, 3-(trimethoxysilyl)propyl 3-oxobutyrate, saturated sodium hydroxide solution, deionized water and anhydrous ethanol is 2-3g:2-3mL:10-15mL:50-60mL:20-30mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed with ethanol and deionized water for 3-5 times, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried to constant weight to obtain modified graphite.

[0020] Furthermore, the method for preparing the explosion-proof fiber comprises the following steps: C1. Azobisisobutyronitrile and o-xylene are placed in a high-pressure reactor, and after propylene is introduced, the temperature of the high-pressure reactor is increased to 200-250° C., the pressure is increased to 15-20 MPa, and the polymerization is carried out at constant temperature and pressure for 40-60 minutes, and then the pressure is released. Flame-retardant graphite is added to the reactor, and the reaction is kept warm for 30-40 minutes. Then, a capping agent is added to the reactor, and the reaction is continued for 10-20 minutes. After the temperature of the reaction liquid is reduced to room temperature, post-treatment is performed to obtain polypropylene fibers; The reaction equation for preparing polypropylene fiber is: Wherein: "·" represents an active free radical.

[0021] The reaction principle for preparing polypropylene fiber is as follows: under high temperature and high pressure, propylene gas is catalyzed by azobisisobutyronitrile to produce free radicals at the surface of o-xylene, and a free radical polymerization reaction occurs. After continuous polymerization, solid polypropylene chain segments are formed. After pressure relief, flame-retardant graphite is added to the solution for chain extension. Finally, after sealing with mercaptopropyltrimethoxysilane, a polypropylene material is obtained. After post-processing and fiberization, polypropylene fiber is obtained.

[0022] C2. Place the polypropylene fiber in a high-pressure reactor, place the high-pressure reactor in a salt bath furnace, use a booster device to introduce carbon dioxide gas into the high-pressure reactor until the internal pressure of the reactor is 18-21 MPa, and obtain explosion-proof fiber after foaming treatment.

[0023] The reaction principle for preparing explosion-proof fibers is as follows: under high temperature and high pressure, carbon dioxide supercritical fluid foaming is performed to form a microporous structure on polypropylene fibers, and finally explosion-proof fibers are prepared.

[0024] Further, in step C1, the amount ratio of azobisisobutyronitrile, o-xylene, propylene, flame retardant graphite and end-capping agent is 0.8-1.2g:40-50mL:18-20g:4-5g:2-3g, the end-capping agent is mercaptopropyltrimethoxysilane, and the post-processing includes: pouring the reaction solution into an electrospinning machine, controlling the voltage of the electrospinning machine to 16-18kV, the receiving distance to 12-16cm, the receiving drum speed to 21-24r / min, and after natural curing, cutting into short fibers with a length of 6-8cm to obtain polypropylene fibers; Furthermore, in step C2, the foaming treatment is as follows: the temperature of the salt bath furnace is raised to 120-140° C., and during the heating process, valves on both sides are used to release air to control the pressure in the reactor to be less than 25 MPa. After the reaction is kept warm for 1-2 hours, the pressure is quickly released.

[0025] The present invention has the following beneficial effects: 1. The present invention prepares a modified flame retardant and grafts it on modified graphite to obtain flame retardant graphite. The flame retardant graphite and the siloxane structure improve the water resistance, acid and alkali resistance and fire resistance of the composite vermiculite, and in the preparation process of the explosion-proof fiber, the polypropylene chain segment has a chain extension effect. Through the hybridization of the chain segment and the excellent physical properties of graphite, the mechanical properties of the polypropylene fiber are significantly enhanced. In the foaming process, the excellent pore structure of the flame retardant graphite promotes the foaming process. Finally, through the synergistic cooperation between materials, the performance of the fire-retardant module is significantly enhanced.

[0026] 2. The present invention is to obtain modified vermiculite by subjecting vermiculite to thermal expansion and surface modification treatment, and to co-polymerize the vermiculite with flame retardant graphite, vinyl silicone oil and 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and to significantly reduce the thermal expansion coefficient of vermiculite by subjecting the vermiculite to thermal expansion pretreatment, and to coordinate with high temperature stable siloxane and graphite structure, so that the heating permanent linear change rate of the heat-resistant module is significantly reduced, and by introducing flame retardant graphite and vinyl silicone oil, the vinyl silicone oil forms a hydrophobic surface on the vermiculite surface. The flame retardant graphite forms a dense physical barrier to hinder water penetration, reduce the polarity of the material surface, and improve hydrophobicity. The two provide dual hydrophobic protection, reduce the exposure of polar sites, further inhibit water absorption, and enhance the water resistance and acid and alkali resistance of the composite material. During the combustion process, the phosphorus-boron composite flame retardant structure on the surface of the flame retardant graphite decomposes, promoting the decomposition of organic chain segments to produce flame-retardant gases and carbonized layers, and by coordinating with the siloxane segments, the fire resistance of the material is significantly enhanced.

[0027] 3. The present invention obtains modified graphite by surface modification after oxidation of graphite, and introduces phosphorus-boron composite flame retardant structure on its chain segment by chain segment modification of diallylamine, and introduces flame retardant chain segment on graphite by nucleophilic addition reaction, which significantly improves the fire resistance of fire-retardant module as flame retardant structure, reduces the polarity of material surface, and improves hydrophobicity; in the process of preparing explosion-proof fiber, the high thermal conductivity of graphite structure prevents heat accumulation and avoids explosion caused by local overheating, and the lamellar structure of graphite prevents crack propagation, improves the strength, impact resistance and durability of fiber, and through graphite The self-lubricating property reduces fiber friction and the risk of high temperature caused by frictional heat generation. In the process of supercritical fluid foaming, the porous characteristics of graphite increase the specific surface area of ​​the material, provide a large number of nucleation sites, significantly increase the nucleation density, and reduce the growth time of bubbles, making the foaming process more efficient and uniform. The porous network can limit the excessive growth of bubbles and prevent bubble aggregation, thereby forming a fine and uniform microporous structure. By adjusting the fiber surface structure, the mechanical properties of the material are significantly enhanced, thereby reducing the occurrence of cracking and powdering during wet heat treatment. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The vinyl silicone oil used in the present invention was purchased from Anhui Mingyi Silicon Industry Co., Ltd., with the product number MY-273.

[0030] Example 1 This embodiment provides a method for preparing modified graphite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step ①: Preparation of graphite oxide Weigh: 100.0g of graphite and 2500.0mL of 98.0wt% concentrated sulfuric acid are added to a reactor and stirred. During the stirring process, 500.0g of potassium permanganate powder is added to the reactor. After stirring at room temperature for 5min, the temperature of the reactor is raised to 30°C, and the reactor is kept warm and stirred for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and a 30wt% aqueous hydrogen peroxide solution is added dropwise to the reactor until the deep purple color of the solution fades, and a saturated sodium hydroxide solution is used to adjust the pH of the reaction liquid system to 7, and then the reaction liquid is filtered to collect the filter cake. After washing the filter cake 3 times with ethanol and deionized water, the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight, and then the material is transferred to a mill and ground through a 600-mesh sieve to obtain graphite oxide.

[0031] Step ②: Preparation of modified graphite Weigh: 200.0 g of graphite oxide, 200.0 mL of 3-(trimethoxysilyl)propyl 3-oxobutyrate, 1000.0 mL of saturated sodium hydroxide solution, 5000.0 mL of deionized water and 2000.0 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 40°C, keep warm and stir for 30 minutes, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake 3 times with ethanol and deionized water, transfer the filter cake to a drying oven at 60°C and vacuum dry to constant weight to obtain modified graphite.

[0032] Example 2 This embodiment provides a method for preparing modified graphite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step ①: Preparation of graphite oxide Weigh: 200.0g of graphite and 4000.0mL of 98.0wt% concentrated sulfuric acid are added to a reactor and stirred. During the stirring process, 1000.0g of potassium permanganate powder is added to the reactor. After stirring at room temperature for 10min, the temperature of the reactor is raised to 45°C, and the reactor is kept warm and stirred for 3h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and a 30wt% aqueous hydrogen peroxide solution is added dropwise to the reactor until the deep purple color of the solution fades, and a saturated sodium hydroxide solution is used to adjust the pH of the reaction liquid system to 7, and then the reaction liquid is filtered to collect the filter cake. After washing the filter cake 5 times with ethanol and deionized water, the filter cake is transferred to a drying oven at 80°C and vacuum dried to constant weight, and then the material is transferred to a mill and ground through an 800-mesh sieve to obtain graphite oxide.

[0033] Step ②: Preparation of modified graphite Weigh: 300.0 g of graphite oxide, 300.0 mL of 3-(trimethoxysilyl)propyl 3-oxobutyrate, 1500.0 mL of saturated sodium hydroxide solution, 5000.0 mL of deionized water and 3000.0 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 50°C, keep warm and stir for 40 minutes, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake with ethanol and deionized water 5 times, transfer the filter cake to a drying oven at 80°C and vacuum dry to constant weight to obtain modified graphite.

[0034] Example 3 This embodiment provides a method for preparing modified graphite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step ①: Preparation of graphite oxide Weigh: 150.0g of graphite and 3600.0mL of 98.0wt% concentrated sulfuric acid are added to a reactor and stirred. During the stirring process, 800.0g of potassium permanganate powder is added to the reactor. After stirring at room temperature for 10min, the temperature of the reactor is raised to 40°C, and the mixture is kept warm and stirred for 3h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, and a 30wt% aqueous hydrogen peroxide solution is added dropwise to the reactor until the dark purple color of the solution fades. After adjusting the pH value of the reaction liquid system to 7 with a saturated sodium hydroxide solution, the reaction liquid is filtered to collect the filter cake. After washing the filter cake 4 times with ethanol and deionized water, the filter cake is transferred to a drying oven at 70°C and vacuum dried to constant weight. The material is then transferred to a mill and ground through a 700-mesh sieve to obtain graphite oxide.

[0035] Step ②: Preparation of modified graphite Weigh: 250.0 g of graphite oxide, 250.0 mL of 3-(trimethoxysilyl)propyl 3-oxobutyrate, 1200.0 mL of saturated sodium hydroxide solution, 5400.0 mL of deionized water and 2400.0 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 45°C, keep warm and stir for 35 minutes, after the reaction is completed, lower the temperature of the reactor to room temperature, filter the reaction liquid and collect the filter cake, wash the filter cake with ethanol and deionized water 4 times, transfer the filter cake to a drying oven at 72°C and vacuum dry to constant weight to obtain modified graphite.

[0036] Example 4 This embodiment provides a method for preparing modified vermiculite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step (1): preparing expanded vermiculite Weigh: 200.0g of vermiculite is transferred to a crucible, and the crucible is placed in a tubular furnace at a temperature of 800°C and a nitrogen atmosphere for 80 seconds. After the material temperature is reduced to room temperature, it is transferred to a grinder and ground through a 600-mesh sieve to obtain expanded vermiculite.

[0037] Step (2): preparing modified vermiculite Weigh: 200.0g expanded vermiculite, 200.0mL vinyltriethoxysilane, 5000.0mL anhydrous ethanol and 2000.0mL deionized water were added into a reactor. After stirring at room temperature for 5 minutes, the temperature of the reactor was increased to 40°C and sodium hydroxide powder was added into the reactor to adjust the pH of the reaction system to 9. The reaction was stirred for 40 minutes. After the reaction was completed, the temperature of the reactor was lowered to room temperature, the reaction liquid was filtered to collect the filter cake, the filter cake was washed 3 times with ethanol and deionized water, and then the filter cake was transferred to a drying oven at 60°C and vacuum dried to constant weight to obtain modified vermiculite.

[0038] Example 5 This embodiment provides a method for preparing modified vermiculite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step (1): preparing expanded vermiculite Weigh: 200.0g of vermiculite is transferred to a crucible, and the crucible is placed in a tubular furnace at a temperature of 900°C and a nitrogen atmosphere for 90 seconds. After the material temperature is reduced to room temperature, it is transferred to a grinder and ground through an 800-mesh sieve to obtain expanded vermiculite.

[0039] Step (2): preparing modified vermiculite Weigh: 300.0g expanded vermiculite, 300.0mL vinyltriethoxysilane, 6000.0mL anhydrous ethanol and 3000.0mL deionized water and add them into a reactor. After stirring at room temperature for 10 minutes, the temperature of the reactor is increased to 60°C and sodium hydroxide powder is added into the reactor to adjust the pH of the reaction system to 10. The reaction is kept warm and stirred for 60 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 5 times with ethanol and deionized water, and the filter cake is transferred to a drying oven at 80°C and vacuum dried to constant weight to obtain modified vermiculite.

[0040] Example 6 This embodiment provides a method for preparing modified vermiculite for a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step (1): preparing expanded vermiculite Weigh: 200.0g of vermiculite is transferred to a crucible, and the crucible is placed in a tubular furnace at a temperature of 850°C and a nitrogen atmosphere for 85 seconds. After the material temperature is lowered to room temperature, it is transferred to a grinder and ground through a 700-mesh sieve to obtain expanded vermiculite.

[0041] Step (2): preparing modified vermiculite Weigh: 250.0g expanded vermiculite, 250.0mL vinyltriethoxysilane, 5400.0mL anhydrous ethanol and 2400.0mL deionized water and add them into a reactor. After stirring at room temperature for 8 minutes, the temperature of the reactor is increased to 50°C and sodium hydroxide powder is added into the reactor to adjust the pH of the reaction system to 10. The reaction is kept warm and stirred for 50 minutes. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 4 times with ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain modified vermiculite.

[0042] Example 7 This embodiment provides a method for preparing an explosion-proof fiber for a waterproof and corrosion-resistant fire-retardant module, comprising the following steps: Step I: Preparation of polypropylene fibers Weigh: 80.0g of azobisisobutyronitrile and 4000.0mL of o-xylene are placed in a high-pressure reactor. After 1800.0g of propylene is introduced, the temperature of the high-pressure reactor is increased to 200°C, the pressure is increased to 15MPa, and the pressure is released after constant temperature and pressure polymerization for 40min. 400.0g of flame-retardant graphite is added to the reactor. After the heat preservation reaction for 30min, 200.0g of mercaptopropyltrimethoxysilane is added to the reactor, and the heat preservation reaction is continued for 10min. After the temperature of the reaction liquid is lowered to room temperature, the reaction liquid is poured into an electrospinning machine, and the voltage of the electrospinning machine is controlled to be 16kV, the receiving distance is 12cm, and the receiving drum speed is 21r / min. After natural curing, it is cut into short fibers with a length of 6cm to obtain polypropylene fibers.

[0043] Step II: Preparation of explosion-proof fiber Weigh: 500.0g of polypropylene fiber is placed in a high-pressure reactor, the high-pressure reactor is placed in a salt bath furnace, and carbon dioxide gas is introduced into the high-pressure reactor using a booster device until the internal pressure of the reactor is 18MPa. The temperature of the salt bath furnace is raised to 120°C. During the heating process, valves on both sides are used to vent gas to control the pressure in the reactor to be less than 25MPa. After the reaction is kept warm for 1h, the pressure is quickly released to obtain explosion-proof fiber.

[0044] Example 8 This embodiment provides a method for preparing an explosion-proof fiber for a waterproof and corrosion-resistant fire-retardant module, comprising the following steps: Step I: Preparation of polypropylene fibers Weigh: 120.0g of azobisisobutyronitrile and 5000.0mL of o-xylene are placed in a high-pressure reactor. After 2000.0g of propylene is introduced, the temperature of the high-pressure reactor is increased to 250°C, the pressure is increased to 20MPa, and the pressure is released after constant temperature and pressure polymerization for 60min. 500.0g of flame-retardant graphite is added to the reactor. After the heat preservation reaction for 40min, 300.0g of mercaptopropyltrimethoxysilane is added to the reactor. The heat preservation reaction is continued for 20min. After the temperature of the reaction liquid is lowered to room temperature, the reaction liquid is poured into an electrospinning machine. The voltage of the electrospinning machine is controlled to be 18kV, the receiving distance is 16cm, and the receiving drum speed is 24r / min. After natural curing, it is cut into short fibers with a length of 8cm to obtain polypropylene fibers.

[0045] Step II: Preparation of explosion-proof fiber Weigh: 500.0g of polypropylene fiber is placed in a high-pressure reactor, the high-pressure reactor is placed in a salt bath furnace, and carbon dioxide gas is introduced into the high-pressure reactor using a booster device until the internal pressure of the reactor is 21MPa. The temperature of the salt bath furnace is raised to 140°C. During the heating process, valves on both sides are used to vent gas to control the pressure in the reactor to be less than 25MPa. After keeping the reaction warm for 2h, the pressure is quickly released to obtain explosion-proof fiber.

[0046] Example 9 This embodiment provides a method for preparing an explosion-proof fiber for a waterproof and corrosion-resistant fire-retardant module, comprising the following steps: Step I: Preparation of polypropylene fibers Weigh: 100.0g of azobisisobutyronitrile and 4500.0mL of o-xylene are placed in a high-pressure reactor. After 1900.0g of propylene is introduced, the temperature of the high-pressure reactor is increased to 240°C, the pressure is increased to 18MPa, and the pressure is released after constant temperature and pressure polymerization for 50min. 450.0g of flame-retardant graphite is added to the reactor. After the reaction is kept warm for 36min, 250.0g of mercaptopropyltrimethoxysilane is added to the reactor. The reaction is continued to be kept warm for 18min. After the temperature of the reaction liquid is lowered to room temperature, the reaction liquid is poured into an electrospinning machine. The voltage of the electrospinning machine is controlled to be 16kV, the receiving distance is 14cm, and the speed of the receiving drum is 21r / min. After natural curing, it is cut into short fibers with a length of 7cm to obtain polypropylene fibers.

[0047] Step II: Preparation of explosion-proof fiber Weigh: 500.0g of polypropylene fiber is placed in a high-pressure reactor, the high-pressure reactor is placed in a salt bath furnace, and carbon dioxide gas is introduced into the high-pressure reactor using a booster device until the internal pressure of the reactor is 20MPa. The temperature of the salt bath furnace is raised to 135°C. During the heating process, valves on both sides are used to vent gas to control the pressure in the reactor to be less than 25MPa. After the reaction is kept warm for 2h, the pressure is quickly released to obtain explosion-proof fiber.

[0048] Example 10 This embodiment provides a method for preparing a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step 1: Preparation of modified flame retardant Weigh: 110.0g of diallylamine, 380.0g of di(pentafluorophenyl)borane, 240.0g of bis(3,5-xylyl)phosphine, 10.0g of chloroplatinic acid and 2100.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 60°C, and keep the reaction for 1h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified flame retardant.

[0049] Step 2: Preparation of flame retardant graphite Weigh: 500.0g of modified graphite prepared in Example 1, 200.0g of modified flame retardant, 30.0g of aluminum chloride and 2700.0mL of toluene are added to the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 11 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 3 times with ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried to constant weight to obtain flame retardant graphite.

[0050] Step 3: Preparation of composite vermiculite Weigh: 400.0g of 4-modified vermiculite prepared in Example 1, 200.0g of flame retardant graphite and 8000.0mL of N,N-dimethylformamide were added to the reactor, stirred at room temperature for 10min, 20mL of vinyl silicone oil, 300.0g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 160.0g of azobisisobutyronitrile were added to the reactor, the temperature of the reactor was raised to 60°C, the mixture was kept warm and stirred for 2h, and the reaction mixture was post-treated to obtain a composite vermiculite. After the reaction was completed, the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 80°C, and the material was transferred to a mill and ground through a 1000-mesh sieve to obtain a composite vermiculite.

[0051] Step 4: Prepare the fire-blocking module Weigh: 2500.0g of composite vermiculite and 800.0g of flame-retardant graphite are added to a stirring kettle. During the stirring process, 4500.0g of chloroprene latex and 200.0g of the explosion-proof fiber prepared in Example 7 are gradually added to the mixture. After mixing evenly, the mixture is added to a mold and shaped at high temperature and high pressure to obtain a fire-retardant module.

[0052] Embodiment 11 This embodiment provides a method for preparing a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step 1: Preparation of modified flame retardant Weigh: 110.0g of diallylamine, 380.0g of di(pentafluorophenyl)borane, 240.0g of bis(3,5-xylyl)phosphine, 30.0g of chloroplatinic acid and 2700.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 80°C, and keep the reaction for 1h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 80°C, and distill under reduced pressure until no liquid is produced to obtain a modified flame retardant.

[0053] Step 2: Preparation of flame retardant graphite Weigh: 600.0g of modified graphite prepared in Example 2, 300.0g of modified flame retardant, 50.0g of aluminum chloride and 3300.0mL of toluene are added to the reactor, the temperature of the reactor is raised to 50°C, and the reaction is kept warm for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 5 times with ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 80°C and vacuum dried to constant weight to obtain flame retardant graphite.

[0054] Step 3: Preparation of composite vermiculite Weigh: 500.0g of the modified vermiculite prepared in Example 5, 300.0g of flame retardant graphite and 10000.0mL of N,N-dimethylformamide were added to the reactor, stirred at room temperature for 15min, 3000.0mL of vinyl silicone oil, 400.0g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 180.0g of azobisisobutyronitrile were added to the reactor, the temperature of the reactor was raised to 80°C, the mixture was kept warm and stirred for 4h, and the reaction was completed after post-treatment. After the reaction was completed, the reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 100°C, and the material was transferred to a mill after reduced pressure distillation until no liquid was extracted, and then ground through a 1200 mesh sieve to obtain a composite vermiculite.

[0055] Step 4: Prepare the fire-blocking module Weigh: 3400.0g of composite vermiculite and 1500.0g of flame-retardant graphite are added to a stirring kettle. During the stirring process, 5500.0g of chloroprene latex and 300.0g of the explosion-proof fiber prepared in Example 8 are gradually added to the mixture. After mixing evenly, the mixture is added to a mold and shaped at high temperature and high pressure to obtain a fire-retardant module.

[0056] Example 12 This embodiment provides a method for preparing a waterproof and anti-corrosion fire-retardant module, comprising the following steps: Step 1: Preparation of modified flame retardant Weigh: 110.0g of diallylamine, 380.0g of di(pentafluorophenyl)borane, 240.0g of bis(3,5-xylyl)phosphine, 20.0g of chloroplatinic acid and 2400.0mL of dimethyl sulfoxide and add them into a reactor, raise the temperature of the reactor to 70°C, and keep the reaction for 2h. After the reaction is completed, cool the reactor to room temperature, add the reaction solution into a rotary evaporator with a water bath temperature of 90°C, and distill under reduced pressure until no liquid is produced to obtain a modified flame retardant.

[0057] Step 2: Preparation of flame retardant graphite Weigh: 550.0g of modified graphite prepared in Example 3, 250.0g of modified flame retardant, 40.0g of aluminum chloride and 3000.0mL of toluene are added to the reactor, the temperature of the reactor is raised to 45°C, and the reaction is kept warm for 2h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 4 times with ethanol and deionized water, and then the filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain flame retardant graphite.

[0058] Step 3: Preparation of composite vermiculite Weigh: 450.0g of modified vermiculite prepared in Example 6, 250.0g of flame retardant graphite and 9000.0mL of N,N-dimethylformamide were added to the reactor, stirred at room temperature for 12min, 2500.0mL of vinyl silicone oil, 350.0g of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and 170.0g of azobisisobutyronitrile were added to the reactor, the temperature of the reactor was raised to 70°C, the mixture was stirred for 3h, and the reaction mixture was post-treated to obtain a composite vermiculite. The reactor was cooled to room temperature, the reaction solution was added to a rotary evaporator with a water bath temperature of 90°C, and the mixture was distilled under reduced pressure until no liquid was extracted. The material was then transferred to a mill and ground through a 1100 mesh sieve to obtain a composite vermiculite.

[0059] Step 4: Prepare the fire-blocking module Weigh: 3000.0g of composite vermiculite and 1200.0g of flame-retardant graphite are added to a stirring kettle. During the stirring process, 5000.0g of chloroprene latex and 250.0g of the explosion-proof fiber prepared in Example 9 are gradually added to the mixture. After mixing evenly, the mixture is added to a mold and shaped at high temperature and high pressure to obtain a fire-retardant module.

[0060] Comparative Example 1 The difference between this comparative example and Example 12 is that the use of vinyl silicone oil is omitted in step 3, and in the preparation process of the modified vermiculite used, step (1) is omitted, and an equal amount of vermiculite powder that has been ground and passed through an 800-mesh sieve is used to replace the expanded vermiculite in step (2).

[0061] Comparative Example 2 The difference between this comparative example and Example 12 is that in step 3, in the process of preparing composite vermiculite, the use of flame retardant graphite is omitted.

[0062] Comparative Example 3 The difference between this comparative example and Example 12 is that during the preparation process of the composite explosion-proof fiber used in step 4, the flame-retardant graphite is omitted in step I.

[0063] Performance Testing: The permanent linear change rate of heating of the fire-blocking modules prepared in Examples 10-12 and Comparative Examples 1-3 was tested with reference to the standard YB / T 4857-2020 "Semi-silica Insulating Refractory Bricks"; The combustion performance grades of the fire-retardant modules prepared in Examples 10-12 and Comparative Examples 1-3 were tested with reference to the standard GB 8624-2012 "Combustion Performance Classification of Building Materials and Products"; With reference to the standard GB 23864-2023 "Fireproof Sealing Materials", the water resistance, acid and alkali resistance, and moisture and heat resistance of the fire-blocking modules prepared in Examples 10-12 and Comparative Examples 1-3 were tested. The water resistance was used to measure the number of days for corrosion of the material, the acid and alkali resistance was used to measure the number of days for swelling or cracking of the material, and the moisture and heat resistance was used to measure the number of days for cracking or powdering of the material. The specific data are shown in Table 1.

[0064] Table 1-Performance test data of each sample Data Analysis: Comparative analysis of the data in Table 1 above shows that the permanent linear change rate of the fire-retardant module prepared by the present invention is 1.4%, the combustion performance grade is A, the water immersion resistance is 12 days, the acid immersion resistance is 13 days, the alkali immersion resistance is 7 days, and the wet heat treatment resistance is 18 days, and all the data are better than the comparative example; The present invention is to obtain modified vermiculite by subjecting vermiculite to thermal expansion and surface modification treatment, and to co-polymerize the vermiculite with flame-retardant graphite, vinyl silicone oil and 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, and to significantly reduce the thermal expansion coefficient of vermiculite by subjecting the vermiculite to thermal expansion pretreatment, and to coordinate with high-temperature stable siloxane and graphite structure, so that the heating permanent linear change rate of the heat-resistant module is significantly reduced, and by introducing flame-retardant graphite and vinyl silicone oil, the vinyl silicone oil forms a hydrophobic surface on the vermiculite surface. The flame retardant graphite forms a dense physical barrier to prevent water penetration, reduce the polarity of the material surface, and improve hydrophobicity. The two provide dual hydrophobic protection, reduce the exposure of polar sites, further inhibit water absorption, and enhance the water resistance and acid and alkali resistance of the composite material. During the combustion process, the phosphorus-boron composite flame retardant structure on the surface of the flame retardant graphite decomposes, promoting the decomposition of organic chain segments to produce flame retardant gases and carbonized layers, and by coordinating with the siloxane chain segments, the fire resistance of the material is significantly enhanced. The present invention obtains modified graphite by surface modification after oxidation of graphite, and introduces phosphorus-boron composite flame retardant structure on its chain segment by chain segment modification of diallylamine, and introduces flame retardant chain segment on graphite by nucleophilic addition reaction, which significantly improves the fire resistance of fire-retardant module as flame retardant structure, reduces the polarity of material surface, and improves hydrophobicity; in the process of preparing explosion-proof fiber, the high thermal conductivity of graphite structure prevents heat accumulation and avoids explosion caused by local overheating, and the lamellar structure of graphite prevents crack propagation, thereby improving the strength, impact resistance and durability of fiber. The self-lubricating property reduces fiber friction and the risk of high temperature caused by frictional heat generation. In addition, during the supercritical fluid foaming process, the porous characteristics of graphite increase the specific surface area of ​​the material, provide a large number of nucleation sites, significantly increase the nucleation density, and reduce the growth time of bubbles, making the foaming process more efficient and uniform. The porous network can limit the excessive growth of bubbles and prevent bubble aggregation, thereby forming a fine and uniform microporous structure. By adjusting the fiber surface structure, the mechanical properties of the material are significantly enhanced, thereby reducing the occurrence of cracking and powdering during the wet heat treatment process. The present invention prepares a modified flame retardant and grafts it onto modified graphite to obtain flame retardant graphite. The flame retardant graphite and the siloxane structure improve the water resistance, acid and alkali resistance and fire resistance of the composite vermiculite, and in the preparation process of the explosion-proof fiber, the polypropylene chain segment is extended. The mechanical properties of the polypropylene fiber are significantly enhanced through the hybridization of the chain segments and the excellent physical properties of the graphite. In the foaming process, the excellent pore structure of the flame retardant graphite promotes the foaming process. Finally, the performance of the fire-retardant module is significantly enhanced through the synergistic cooperation between the materials.

[0065] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a waterproof and anti-corrosion fire-retardant module, characterized in that: The following steps are involved: S1. Add diallylamine, di(pentafluorophenyl)borane, bis(3,5-xylyl)phosphine, chloroplatinic acid and dimethyl sulfoxide into a reactor, raise the temperature of the reactor to 60-80°C, keep the reaction temperature for 1-2h, and post-treat to obtain a modified flame retardant; S2, adding modified graphite, modified flame retardant, aluminum chloride and toluene into a reactor, raising the temperature of the reactor to 40-50° C., keeping the temperature for reaction for 1-2 hours, and post-treating to obtain flame retardant graphite; S3, adding modified vermiculite, flame retardant graphite and N, N-dimethylformamide into a reactor, stirring at room temperature for 10-15 minutes, adding vinyl silicone oil, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and azobisisobutyronitrile into the reactor, raising the temperature of the reactor to 60-80°C, keeping warm and stirring for 2-4 hours, and post-treating to obtain composite vermiculite; S4. Add composite vermiculite and flame-retardant graphite into a stirring kettle, gradually add chloroprene latex and explosion-proof fiber into the mixture during stirring, add the mixture into a mold after mixing evenly, and shape it under high temperature and high pressure to obtain a fire-retardant module.

2. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 1, characterized in that: In step S1, the amount ratio of diallylamine, di(pentafluorophenyl)borane, bis(3,5-xylyl)phosphine, chloroplatinic acid and dimethyl sulfoxide is 1.1g:3.8g:2.4g:0.1-0.3g:21-27mL; in step S2, the amount ratio of modified graphite, modified flame retardant, aluminum chloride and toluene is 5-6g:2-3g:0.3-0.5g:27-33mL.

3. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 1, characterized in that: In step S3, the amount ratio of modified vermiculite, flame retardant graphite, N,N-dimethylformamide, vinyl silicone oil, 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and azobisisobutyronitrile is 4-5g:2-3g:80-100mL:20-30mL:3-4g:1.6-1.8g; in step S4, the amount ratio of composite vermiculite, flame retardant graphite, chloroprene latex and explosion-proof fiber is 25-34g:8-15g:45-55g:2-3g.

4. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 1, characterized in that: The preparation method of the modified vermiculite comprises the following steps: A1. After transferring the vermiculite into a crucible, the crucible is placed in a tubular furnace at a temperature of 800-900° C. and a nitrogen atmosphere for 80-90 seconds, and then post-processed to obtain expanded vermiculite; A2. Add expanded vermiculite, vinyl triethoxysilane, anhydrous ethanol and deionized water into a reactor, stir for 5-10 minutes at room temperature, increase the temperature of the reactor to 40-60°C, add sodium hydroxide powder into the reactor to adjust the pH value of the reaction system to 9-10, keep warm and stir for 40-60 minutes, and perform post-treatment to obtain modified vermiculite.

5. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 4, characterized in that: In step A1, post-treatment includes: after standing, after the temperature of the material drops to room temperature, transferring it to a grinder, grinding it through a 600-800 mesh sieve to obtain expanded vermiculite; in step A2, the amount ratio of expanded vermiculite, vinyl triethoxysilane, anhydrous ethanol and deionized water is 2-3g:2-3mL:50-60mL:20-30mL.

6. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 1, characterized in that: The preparation method of the modified graphite comprises the following steps: B1. Add graphite and 98.0wt% concentrated sulfuric acid into a reactor and stir. Add potassium permanganate powder into the reactor during stirring. Stir for 5-10 min at room temperature. Then, raise the temperature of the reactor to 30-45°C, keep stirring for 2-3 h, and perform post-treatment to obtain graphite oxide. B2. Add graphite oxide, 3-(trimethoxysilyl)propyl 3-oxobutyrate, saturated sodium hydroxide solution, deionized water and anhydrous ethanol into a reactor and stir. Raise the temperature of the reactor to 40-50° C., keep stirring for 30-40 minutes, and perform post-treatment to obtain modified graphite.

7. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 6, characterized in that: In step B1, the ratio of graphite, 98.0wt% concentrated sulfuric acid and potassium permanganate is 1-2g:25-40mL:5-10g; In step B2, the amount ratio of graphite oxide, 3-(trimethoxysilyl)propyl 3-oxobutyrate, saturated sodium hydroxide solution, deionized water and anhydrous ethanol is 2-3 g: 2-3 mL: 10-15 mL: 50-60 mL: 20-30 mL.

8. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 1, characterized in that: The method for preparing the explosion-proof fiber comprises the following steps: C1. Azobisisobutyronitrile and o-xylene are placed in a high-pressure reactor, and after propylene is introduced, the temperature of the high-pressure reactor is increased to 200-250° C., the pressure is increased to 15-20 MPa, and the polymerization is carried out at constant temperature and pressure for 40-60 minutes, and then the pressure is released. Flame-retardant graphite is added to the reactor, and the reaction is kept warm for 30-40 minutes. Then, a capping agent is added to the reactor, and the reaction is continued for 10-20 minutes. After the temperature of the reaction liquid is reduced to room temperature, post-treatment is performed to obtain polypropylene fibers; C2. Place the polypropylene fiber in a high-pressure reactor, place the high-pressure reactor in a salt bath furnace, use a booster device to introduce carbon dioxide gas into the high-pressure reactor until the internal pressure of the reactor is 18-21 MPa, and obtain explosion-proof fiber after foaming treatment.

9. The method for preparing a waterproof and anti-corrosion fire-retardant module according to claim 8, characterized in that: In step C1, the amount ratio of azobisisobutyronitrile, o-xylene, propylene, flame retardant graphite and end-capping agent is 0.8-1.2g:40-50mL:18-20g:4-5g:2-3g, and the end-capping agent is mercaptopropyltrimethoxysilane; in step C2, the foaming treatment is: the temperature of the salt bath furnace is raised to 120-140°C, and the valves on both sides are used to release air during the heating process to control the pressure in the reactor to be less than 25MPa. After the reaction is kept warm for 1-2h, the pressure is quickly released.

Citation Information

Patent Citations

  • Thermosetting resin base fire retardant module

    CN101798195B

  • Preparation method of DOPO-cooperated MOSS-6 flame-retardant PC composite material

    CN114456570A

  • Method for preparing flame-retardant wear-resistant plastic plate by regenerating waste plastic

    CN119391150A